2019
DOI: 10.1108/mbe-12-2018-0103
|View full text |Cite
|
Sign up to set email alerts
|

The potential beyond IC 4.0: the evolution of business intelligence towards advanced business analytics

Abstract: Purpose The private health care sector is seeking to improve their understanding of business processes to be able to improve their performance. The purpose of this paper is to understand the future needs of the private health care sector organizations in terms of business intelligence (BI) and business analytics (BA) to ensure value creation. Design/methodology/approach The four evolution stages of intellectual capital enriched by managerial data-driven approach are used as a framework to point out the futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Big data manage structural capital to ensure timely and appropriate data availability for strategic decisions. (Ratia, 2019). Along with that, organizations that hope to find opportunities such as altering their operations, innovating their markets, and effectively serving their customers can invest in BDA for further value creation (Ratten, 2020;Brown et al, 2011).…”
Section: The Nexus Between Structural Capital and Big Datamentioning
confidence: 99%
“…Big data manage structural capital to ensure timely and appropriate data availability for strategic decisions. (Ratia, 2019). Along with that, organizations that hope to find opportunities such as altering their operations, innovating their markets, and effectively serving their customers can invest in BDA for further value creation (Ratten, 2020;Brown et al, 2011).…”
Section: The Nexus Between Structural Capital and Big Datamentioning
confidence: 99%
“…Thanks to predictive and prescriptive analysis, BDA represents an efficient choice and a new method to unlock, manage, measure and report intangible resourcesmade up of human, relational and structural capitalthus helping policy makers to identify policies and practices by IC (Dumay and Guthrie, 2019). For example, physical, emotional and social factors (HC ) managed with analytics favour more efficient decisionmaking processes; RC improves interaction with stakeholders in terms of data sharing and SC provides timely and relevant data for strategic decisions (Ratia, 2019). The real added value of BDA, having access to valuable information (big data), lies in the ability to identify not only explicit but also tacit knowledge and in its ability to share it.…”
Section: Discussionmentioning
confidence: 99%
“…These main articles are evident in Table 2 3.2 Descriptors: BDA, IC, and health performance The systematic review of the literature has revealed that a new phase of IC research, the fifth phase (Harlow, 2018), has emerged in recent years, in which the importance of BDA to develop IC in different organizations is underlined. Indeed, an innovative management of IC components, linked to the use of BA in the IC model, represents an important strategic asset for improving efficiency and for creating value in healthcare systems (Maditinos et al, 2011;Ratia et al, 2019). This conception is based on the assumption that IC includes all the knowledge of the company: human, relational and structural capital (Nahapiet and Ghoshal, 1998;Youndt et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, several scholars have analyzed the role of IC on company performance, growth and competitiveness (Alipour, 2012;Parshakov, 2017;Ratia et al, 2019;Sanchez-Gutierrez et al, 2016); however, the importance of IC after the financial crisis (Kehelwalatenna, 2016) has not yet been fully investigated. The rise of new mechanismssuch as the ECFin response to this crisis offers the opportunity to explore the impact of IC in new contexts.…”
Section: Introductionmentioning
confidence: 99%